Validation of a blood protein signature for non-small cell lung cancer - Mehan, Michael R.; Williams, Stephen A.; Siegfried, Jill M.; Bigbee, William L.; Weissfeld, Joel L.; Wilson, David O.; Pass, Harvey I.; Rom, William N.; Muley, Thomas; Meister, Michael; Franklin, Wilbur; Miller, York E.; et al. (Clinical proteomics, 2014)
CT screening for lung cancer is effective in reducing mortality, but there are areas of concern, including a positive predictive value of 4% and development of interval cancers. A blood test that could manage these limitations would be useful, but development of such tests has been impaired by variations in blood collection that may lead to poor reproducibility across populations.
Gesehen am 16.02.2021